Is The Exchange Rate The Most Important Determinants of China Trade Balance with United States? - Hong, Sheng (2010)
This study explores the determinants of the USA’s trade balance (NE) with China, and tests for long-run relationships. Regression results suggest the model involving the real exchange rate and the inflation (or price) ratio together demonstrate a better result than the nominal exchange rate by Johansen’s method. The estimated NE regression model shows most important determinant of NE is the money supply ratio (USA relative to China), followed by the GDP per capita ratio, real exchange rate, the lending rate, and the inflation ratio, which together explain 97% of the variation in NE. This implies that besides the most commonly believed factor - exchange rate, money supply ratio and GDP per capita ratio also play important roles determining the Sino-U.S. trade balance. Johansen’s cointegration test suggests a significant (at 1%) long run relationship between NE and its determinants. As referring to relationship between NE and the real exchange rate (ER), Engle-Granger test suggests that there is a negative long run relationship between NE and the exchange rate (ER) at 5% if ER shocks precede NE shocks, which reinforce the cointegration results. Meanwhile, results based on the Error Correction Model (ECM) suggest a positive short term relationship between expected real exchange rate (RER) and trade balance. It may be used to monitor and predict NE, given relevant values (predicted or predetermined) of the determinants. Meanwhile, if the U.S. aims to change the expanding trade deficit in near future, one practical way recommended by this paper is to change the RMB exchange regime from U.S. dollar peg to the free floating in a progressive way.